Agronomic adaptive strategies to strengthen smallholder farmers’ resilience to climate change - CGIAR System Organization (CGIAR System Organization, 2022)
The brief explains about the importance of climate adaptation and the entry points for agronomic adaptation to strengthen resilience of smallholder farmers to climate change